ORAL HYGIENE HABITS IN COMPLETE DENTURE WEARERS - Nickolay Apostolov; Stefan Zlatev; Bozhidar Yordanov; Mariana Yankova; Rangel Todorov (Peytchinski Publishing, 2022)
Aim: The aim of the present research is to establish the frequency and methods of cleaning used by patients with complete dentures. Material and Methods: A survey was conducted between 2016 and 2019 among 96 patients (54 female and 42 male). This study was carried out at the faculty of dental medicine, Medical University - Sofia, during the students' classes in Clinical Prosthetic Dental Medicine and Oral Surgery. A survey card was prepared, including questions addressing the period of total edentulism, a periodor rehabilitation with complete dentures, methods and frequency of cleaning and types of hygienic products used by the compete denture wearers. Descriptive statistics, graphical analysis, chi-square test and correlation analysis were computed in R. Results: Only 12 % of the respondents clean their dentures properly. Nearly 60% of the patients report a widespread but incorrect cleaning method using toothbrushesnd toothpaste, and more than 25% use inappropriate, old, and disregarded hygienic means. 65% clean their dentures twice per day. The research showed a strong positive correlation between age and the time wearing dentures. Conclusion: The findings from the current survey suggest that complete denture wearers are either unaware or negligible towards the proper maintenance of their prostheses.